THE USE OF SOCIAL MEDIA AND LEARNING MEDIA TECHNOLOGY DURING PANDEMIC COVID-19 - Misla Geubrina (Institut Pendidikan Tapanuli Selatan, 2021)
After the emergence of the Covid-19 outbreak, the education system began to look for an innovation for the process of teaching and learning activities. Many educational institutions use social media and e-learning-based learning media technology to support this learning.This study aims to determine the use of social media and learning media technology during pandemic covid-19which has spread throughout the world, especially Indonesia. The social media and learning media technologiesare Google Classroom, Zoom, Google Hangout Meet, YouTube and WhatsApp platforms. The research used a qualitative approach by collecting data with literature study then the results show that social media and learning media technology has many roles and benefits in the world of education, especially during distance learning in the midst of the Covid-19 pandemic. It can be concluded that thesocial media and learning media technology that is widely used by teachers and students are WhatsApp Group, Google Classroom, Google Hangout Meet, Zoom and YouTube.The use of appropriate social media and learning media can affect the learning outcomes of students, starting from the psychomotor, effective, and cognitive aspects.